Is there a relationship between loneliness and academic performance? - Ortega, Florie D. (1999)
The relationship between loneliness and academic performance is the most important part of this study. There were 80 respondents (20 for each year level) of the U.P. Tacloban College who were given a questionnaire to measure the degree of their loneliness. After the tabulation of the gathered data together with the obtained GWA of the preceding grading period, descriptive statistics particularly Pearson's r- correlation coefficient was used. The resulting relationship was very weak with a product of =.89 which means that loneliness has nothing to do with academic performance. However, a very striking inverse relationship between loneliness and number of female friends was represented with -.99, so that the more the number of female friends, the less lonely they become.